The Relation Between Preschoolers' Vocabulary Development and Their Ability to Predict and Recognize Words. Issue 3 (31st August 2020) - Gambi, Chiara; Jindal, Priya; Sharpe, Sophie; Pickering, Martin J.; Rabagliati, Hugh
Abstract : By age 2, children are developing foundational language processing skills, such as quickly recognizing words and predicting words before they occur. How do these skills relate to children's structural knowledge of vocabulary? Multiple aspects of language processing were simultaneously measured in a sample of 2‐to‐5‐year‐olds ( N = 215): While older children were more fluent at recognizing words, at predicting words in a graded fashion, and at revising incorrect predictions, only revision was associated with concurrent vocabulary knowledge once age was accounted for. However, an exploratory longitudinal follow‐up ( N = 55) then found that word recognition and prediction skills were associated with rate of subsequent vocabulary development, but revision skills were not. We argue that prediction skills may facilitate language learning through enhancing processing speed.